Implementasi Program Asuransi Usaha Tani Padi (Autp) di Kabupaten Tabanan Tahun 2023 - Utami, Ni Made Astuti Wahyu; Wiguna, I Made Ananda (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The aim of this research is to describe and determine the implementation of the Rice Farming Business Insurance Program (AUTP) in Tabanan Regency. The theory used in this research is the implementation model theory by Edward III. This type of research uses descriptive qualitative. The results of this research show that (1) the focus of communication in the implementation of the Rice Farming Business Insurance Program (AUTP) in Tabanan Regency has been carried out well, (2) the focus of resources in implementing the Rice Farming Business Insurance Program (AUTP) in Tabanan Regency has not been implemented well. This can be seen that the number of existing officers is not sufficient to cover the AUTP Program in the Tabanan Regency area. Then there are guidelines for implementing the AUTP program which are used by officers. (3) In terms of disposition focus in implementing the Rice Farming Business Insurance Program (AUTP) in Tabanan Regency, it can be said to have been implemented well. This can be seen that the officers have a good understanding of the provisions of the AUTP program in Tabanan Regency, (4) The focus on the bureaucratic structure in implementing the AUTP program in Tabanan Regency has been implemented well.